Comparison of the clinical effects of robot-assisted total mesorectal excision and transanal total mesorectal excision - Zhang Cheng; Duan Fuxiao; Li Da; Gao Guangrong; Ma Rui (结直肠肛门外科)
[Objectives] To compare the clinical effects of robot-assisted total mesorectal excision (RoTME) and transanal total mesorectal excision (taTME) in the treatment of low rectal cancer. [Methods] A retrospective analysis was conducted on the clinical data of 58 patients with low rectal cancer admitted to the General Hospital of Northern Theater Command of the Chinese People’s Liberation Army from January 2021 to June 2023. Based on the surgical approach, patients were divided into the RoTME group (n=27) and the taTME group (n=31). Oncologic indicators, safety indicators, and anal and urinary function indicators were compared between the two groups. [Results] The distance of the distal resection margin was significantly closer in the taTME group compared to the RoTME group (P<0.001). High-quality mesorectal excision was achieved in 29 cases (93.5%) in the taTME group and all 27 cases in the RoTME group, with no statistically significant difference (P=0.494). No significant differences were observed between the two groups in terms of maximum tumor diameter, number of lymph nodes dissected, and pathological tumor node metastasis stage (P>0.05). All surgeries were completed without conversion to open surgery or intraoperative blood transfusion. Postoperative complications occurred in 6 patients, with 4 Clavien-Dindo grade Ⅱ complications in the taTME group and 2 in the RoTME group, showing no statistically significant difference in complication rates (P>0.05). Ten patients (37.0%) in the RoTME group underwent prophylactic end ileostomy. No significant differences were found in operative time, intraoperative blood loss, and hospital stay between the two groups (P>0.05). The postoperative Wexner incontinence score, low anterior resection syndrome (LARS) scores, and International Prostate Symptom Score (IPSS) in the RoTME group were higher than those in the taTME group, and the differences were statistically significant (P<0.05). The score of the International Consultation on Incontinence Modular Questionnaire on Male/Female Lower Urinary Tract Symptoms Scale (ICIQ-MLUTS/FLUTS) for males in the RoTME group was higher than that in the taTME group, and the difference was statistically significant (P<0.05). There was no statistically significant difference (P>0.05) in the scores of the ICIQ Scale between the two groups of women after surgery. [Conclusion] Both RoTME and taTME are safe and effective surgical options for low rectal cancer. taTME provides a more precise determination of the distal resection margin and may better preserve male urinary function, but it has a greater impact on postoperative anal function.